Kepuasan Pasien Peserta JKN Pada Mutu Pelayanan Kefarmasian di Puskesmas Induk Wilayah Surakarta - Nila Darmayanti Lubis; Santi Dwi Astuti (Jurnal Farmasi Indonesia, 2018)
In the era of National Health Insurance, health development in the field of medicine, amongothers, aims to ensure the availability of medicines to achieve satisfactory service targets. Thesurvey of the Directorate General of Pharmacy and Medical Devices at the Ministry of Healthshows that health care centers that have implemented pharmaceutical services according to thenew standards have reached 25%. The purpose of this study was to determine the percentage ofpatient satisfaction of participants of the National Health Insurance in the quality of pharmacyservices at the Parent Community Health Center in Surakarta.This research is a quantitative study, data obtained concurent. Primary data were obtainedfrom questionnaires filled by outpatient National Health Insurance patients. Informants wereselected using purposive sampling technique. Questionnaire data was processed then comparedbetween the services obtained by the patient and the services expected by the patient, after whichthe results were presented in the form of a Cartesian diagram.Through this research, 90.23% of National Health Insurance patients at the Surakartaprimary health center expressed satisfaction with the quality of their pharmaceutical services andservices in accordance with patient expectations.